A OIT, o Ministério do Trabalho e Emprego, e o Ministério Público do Trabalho: o “trabalho decente” no Brasil - Márcia Regina Barroso (Ciências Sociais Unisinos)
This paper refers to a broader research focused on the trajectory of the International Labour Organization (ILO) in Brazil. As an important institution in the Brazilian labor scene, the ILO has currently excelled in projects that move around the idea of decent work. Through intense cooperation with other institutions, the ILO has exerted great influence on the so-called “world of work”. In this sense, I have performed a mapping of themes and areas of social and political articulation primarily engendered between the ILO, the Labor Prosecution Office, and the Ministry of Labor and Employment, focusing on an analysis of the dissemination of the policy of decent work. I think that through this mapping it is possible to identify, on the basis of these privileged spaces, relevant themes and guidelines for the field of labour in Brazil. For this purpose, I conducted an extensive bibliographic and documentary research, prioritizing information about actions of the ILO in Brazil.